Human Capital and Growth Mindset Influence the Performance of MSMES through Psychological Capital as a Moderator Variable - unm, inanna; Dia; Supatminingsih, Tuti; Said, Muh Ihsan; Subur, Hikmayani (MultiTech Publisher, 2024)
This study was conducted to examine how Human Capital and Growth Mindset influence the performance of MSMEs in Enrekang Regency through Psychological Capital. The purpose of this research is to improve MSME performance by developing human capital and a growth mindset, as well as enhancing the quality of psychological capital among MSME actors. The study used a sample of 100 MSME actors in Enrekang Regency, selected using purposive sampling techniques. Data were collected through questionnaires and analyzed. The analytical method employed is Partial Least-Square Structural Equation Modeling (PLS-SEM). The results of the study show that human capital and growth mindset have a positive and significant effect on MSME performance. Additionally, psychological capital is proven to moderate the relationship between human capital and MSME performance, as well as between growth mindset and MSME performance